The Effect of Cobalt Loading on Fischer Tropsch Synthesis Over Silicon Carbide Supported Catalyst - Lee, Jae Suk; Jung, Jae Sun; Moon, Dong Ju (AMER SCIENTIFIC PUBLISHERS, 2015)
A series of Co (5-30 wt%) based SiC supported catalysts were prepared by impregnation method and investigated for FT'S reaction. The FTS reaction was carried out in a fixed bed reactor system with the H-2/CO molar ratio of 2, reaction temperature of 230 degrees C and reaction pressure of 20 bar for 120 h. All catalysts were characterized by N-2 physisorption, XRD, TPR, SEM and TEM techniques. It was found that 15 wt% Co/SiC catalyst showed better catalytic performance with high selectivity of C5+ hydrocarbons than the other catalysts. The results, suggest that the catalytic performance of the catalysts depends on average pore size of support and surface density of cobalt, metal and support interactions.